Teaching Assistants in Canadian Universities: An Unknown Resource - Piccinin, Serge J.; Farquharson, Andy; Mihu, Elena (Canadian Journal of Higher Education, 1993)
Teaching Assistants (TAs) play an important role in most major universities. Interest in the training and development of TAs has increased in recent years, particularly in the U.S.A. In Canada very little research has been conducted regarding the work and status of TAs. The study provides a portrait of TAs in Canadian universities: their number, roles, remuneration, preparation and training, and policies governing their duties and responsibilities. Many universities had only a limited knowledge of the number of TAs employed, their qualifications for the tasks they are assigned and their training and supervision. The need for improving TA experience is clear and the establishment of a National Clearinghouse of TA-related materials is proposed.